Impact of green space on residents' wellbeing: A case study of the Grand Canal (Hangzhou section) - Xia, Yuke (Frontiers in Public Health, 2023)
Introduction In this study aimed to discuss the importance of the combination of cultural heritage management and green development for urban development by analyzing the upgrading and renovation of the Grand Canal (Hangzhou section) as a successful case. In recent years, green development has risen to prominence as a paradigm shift. Additionally, culture, as an engine to drive urban development, has received more attention. Methods This research used a hybrid approach to examine the importance of combining green development with cultural heritage management. The qualitative method was an interview analysis of 13 residents living in the Hangzhou section of the Grand Canal. Based on the analysis of multiple water quality variables in Hangzhou from 1998 and 2014 to 2021, the empirical results proved that it is feasible to integrate green development (environment and economy) into the cultural heritage management of the case study area. Results and discussion The results further prove that only through an understanding of the relationship between cultural heritage and green development can a virtuous cycle of development be created, thereby promoting the continuous development of a unique and historically significant urban area. The results of this study suggest that, in the development of mega-cities, although the preservation and inheritance of historical and cultural heritage conflicts with the green development of modern cities, a successful example has been explored in Hangzhou, including grassroots governance efforts like Gongshu District. There, the two factors can be mutually compatible and promote each other, enhancing the well-being and happiness of local residents.